The Minoan Thera eruption predates Pharaoh Ahmose: Radiocarbon dating of Egyptian 17th to early 18th Dynasty museum objects - Hendrik J. Bruins; Johannes van der Plicht (PLoS ONE, 2025)
The huge volcanic eruption at Thera (Santorini), situated in the Aegean Sea, occurred within the Late Minoan IA archaeological period. However, its temporal association with Egyptian history has long been a controversial subject. Traditionally, the eruption was placed in the early 18th Dynasty, associated with Pharaoh Thutmose III as the youngest option or with Pharaoh Nebpehtire Ahmose as the oldest possibility. We investigated museum objects from the 17th and early 18th Dynasty, at the transition from the Second Intermediate Period to the New Kingdom, a period hardly studied with radiocarbon dating. Our research facilitated the first-ever direct radiocarbon time comparison between this Dynastic transition period and the Minoan Thera eruption. Detailed results are presented of a mudbrick from the Ahmose Temple at Abydos (British Museum), a linen burial cloth associated with Satdjehuty (British Museum), and wooden stick shabtis from Thebes (Petrie Museum), evaluated within a comprehensive context of historical Egyptian chronology options. Since the above items cannot be arranged in a stratigraphic sequence, Bayesian analysis could not be used. We adopted an alternative strategy within radiocarbon time space. Comparing our uncalibrated dates of 17th and early 18th Dynasty objects with a robust series of uncalibrated radiocarbon dates for the Minoan Thera eruption, it becomes clear that the two data sets have a different time signature. The Minoan eruption is older than the reign of Nebpehtire Ahmose, the first king of the 18th Dynasty, who reunited Upper and Lower Egypt. Our calibrated results support a low chronology for his reign and the beginning of the New Kingdom. Previous radiocarbon dates of king Senusert III support a high chronology for the Middle Kingdom. Therefore, the Second Intermediate Period, sandwiched in between these united Egyptian Kingdoms, embodies a significant time interval, as also indicated by Bennett’s genealogical studies of the El-Kab governors.